HYPER-SOLUBILIZING TRICALCIUM PHOSPHATE MUTANTS OF Klebsiella sp. GMD08 - Nur Fitriana Ariyanti; Jaka Widada; Siti Subandiyah (SEAMEO BIOTROP, 2020)
Klebsiella sp. GMD08 is a bacterium capable of dissolving insoluble inorganic phosphate into soluble phosphate ions through its organic acid production. Transposon is a genetic element commonly used to generate mutants through mutagenesis, and thus can be used to identify genetic functions involved in phosphate-solubilizing mechanisms. This research was conducted to identify the genes of Klebsiella sp. GMD08 involved in phosphate solubilization through sequence detection obtained from a hyper-solubilizing phosphate mutant library. Mutation was carried out by inserting a mini-Tn5 transposon hosted in Escherichia coli S17-1/λpir [pBSL202] into the chromosome of Klebsiella sp. GMD08 using the filter mating conjugation method. Transconjugant mutant candidates were then qualitatively and quantitatively analyzed for their ability to dissolve tricalcium phosphate [Ca₃(PO₄)₂] using Pikovskaya medium. The organic acid profiles of the transconjugant mutants were detected using High-Performance Liquid Chromatography (HPLC). Suspected genes involved in phosphate solubilization were identified through sequencing of transposon insertion sites. Nucleotide BLAST was used to determine nucleotide sequence similarity with the database. The results showed that PB116 and PB122 were the two main transconjugant mutants obtained from transposon mutagenesis with higher tricalcium phosphate-dissolving ability. Gluconic acid was identified as the main organic acid produced by Klebsiella sp. GMD08 in its phosphate-solubilizing mechanism. Furthermore, the arginine repressor (ArgR) and malate dehydrogenase (mdh) genes were found to be involved in the phosphate-solubilizing mechanism of Klebsiella sp. GMD08.